Good Practices for Financial Consumer Protection - World Bank (Washington, DC, 2017)
Financial consumer protection sets clear rules of conduct for financial firms regarding their retail customers. It aims to ensure that consumers: 1) receive information to allow them to make informed decisions, 2) are not subject to unfair or deceptive practices, and 3) have access to recourse mechanisms to resolve disputes. Complementary financial literacy initiatives are aimed at giving consumers the knowledge and skills to understand the risks and rewards of using financial products and services-and their legal rights and obligations in using them. Clear rules of conduct for financial institutions, combined with programs of financial education for consumers, will increase consumer trust in financial markets and will support the development of these markets. International and regional non-government organizations are also playing an increasingly important role in financial consumer protection. The responsible finance forum lists financial consumer protection regulation and financial capability as two of the three pillars of the framework for responsible finance. This summary is not exhaustive but helps illustrate the many ongoing international initiatives that support financial consumer protection. All the initiatives are helpful in strengthening the global response to weaknesses in financial consumer protection. Nevertheless, still more could be done by civil society organizations, particularly those operating at a global level. The World Bank is also supporting the international dialogue on financial consumer protection through development of good practices based on country-level experience and ongoing technical assistance. The good practices provide a comprehensive diagnostic tool to help identify the consumer protection issues in all parts of the financial sector.